Distributed computing and internet technology : 14th International Conference, ICDCIT 2018, Bhubaneswar, India, January 11-13, 2018, Proceedings /: 14th International Conference, ICDCIT 2018, Bhubaneswar, India, January 11-13, 2018, Proceedings. (2018) - Unknown
No abstract available